Distance Still Matters: Evidence from Municipal Bond Underwriting - Butler, Alexander W. (Review of Financial Studies, 2008)
Using a sample of municipal bond offerings, I find that "local" investment banks have substantial comparative and absolute advantages over nonlocal counterparts—locals charge lower fees and sell bonds at lower yields. Local investment banks' strongest comparative advantage is at underwriting bonds with higher credit risk and bonds not rated by rating agencies. These findings suggest that high-risk bonds and nonrated bonds are more difficult to evaluate and market, and that investment banks with a local presence are better able to assess "soft" information and place difficult bond issues. The Author 2008. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please email: journals.permissions@oxfordjournals.org, Oxford University Press.